Magnetic Resonance Imaging of Bacterial Meningoencephalitis in a Foal. (9th September 2012) - Viu, Judit; Armengou, Lara; de la Fuente, Cristian; Cesarini, Carla; Añor, Sònia; Jose-Cunilleras, Eduard
Abstract : Magnetic resonance imaging (MRI) in equidae suffering meningoencephalitis (ME) has not been described. The objective of this paper is to describe brain MRI findings in a foal with bacterial ME. A five-month-old, 200 kg bwt Arabian filly was referred with a history of abnormal mental status and locomotion. The filly was recumbent and obtunded, and pupillary light reflexes were sluggish, and oculocephalic movements were normally present. Ophthalmic examination revealed bilateral optic neuritis. Hematology revealed leukocytosis and neutrophilia. Cerebrospinal fluid analysis showed neutrophilic pleocytosis with intracellular bacteria. On brain MRI, there were multifocal cortical areas of mild hyperintensity on T2-weighted images (T2WI) affecting both hemispheres. The lesions had ill-delineated margins, and there was loss of differentiation between gray and white matter. Diffuse hyperintensity was also identified in the left cerebellar cortex on T2WI. Neither mass effect nor cerebral midline shift were identified. On FLAIR images, the lesions were also hyperintense and, in some areas, they seemed to coalescence to form diffuse cortical areas of hyperintensity. The MRI findings described were similar to the MRI features described in cases of humans and small animals with ME. Brain MRI can be a useful diagnostic tool in foals and small-sized equidae with intracranial disease.